Existence of positive solutions for certain partial difference equations (Discrete Dynamics in Nature and Society)
We give some sufficient conditions for the existence of positive solutions of partial difference equation a A m+1,n+1 +b A m,n+1 +c A m+1,n −d A m,n + P m,n A m−k,n−1 =0 by two different methods.